Penegakan Hukum Dalam Keterlambatan Pembayaran Pajak Kendaraan Bermotor Di Kabupaten Tabanan - I Putu Yudi Setiawan; Ida Ayu Putu Widiati; Luh Putu Suryani (Warmadewa Press, 2024)
The increase in population has led to a rapid increase in motor vehicle ownership. Motorized vehicles have become a basic necessity for some people. Ownership of motorized vehicles will be followed by obligations as taxpayers who must make tax payments. However, increasing the number of motor vehicle ownership does not necessarily increase public awareness to be obedient and aware of the obligation to pay taxes. This can lead to legal consequences for both the community and the government. This research aims to find out the regulation in the field of taxes responding to the lack of public awareness of tax payments. With the main problems that will be discussed in this study, namely 1) how is law enforcement in late payment of motor vehicle tax in Tabanan Regency, 2) What are the inhibiting factors in the enforcement of late payment of motor vehicle tax in Tabanan Regency. The research method used is an empirical research method, with a fact approach and legal concept analysis approach. The results of law enforcement in late payment of motor vehicle tax in Tabanan Regency are given a PKB notification letter given a notification letter of STNK validation and a late notice of tax payment, if it has not been replied to from the taxpayer, UPTD PPRD Bali Province in Tabanan Regency will impose penalties on taxpayers such as administrative penalties for interest / fines and inhibiting factors are the lack of awareness of taxpayers in paying motor vehicle taxes, transferring motorized vehicles without transferring names, vehicle owners moving residence.